Cardiac Considerations in Treatment of Schizophrenia: A Case Report Highlighting the Use of Long-acting Injection Paliperidone Palmitate Depot in Schizophrenia Patient with Comorbid Wolff-Parkinson-White Syndrome - Suparna Kumar; Sangha Mitra Godi (Indian Journal of Private Psychiatry)
The effect of antipsychotics on electron-conduction abnormalities in already diagnosed Wolff-Parkinson-White (WPW) syndrome is under-evaluated which creates a dilemma among practitioners in choosing an effective antipsychotic with minimal side effects. Paliperidone, a second-generation antipsychotic, is Food and Drug Administration (FDA) approved for treating schizophrenia, but the studies have documented mixed results on its effect on QT prolongation. Hence, we are going to present a case of paranoid schizophrenia with comorbid WPW syndrome showing a remarkable response on long-acting paliperidone palmitate depot with no effect on QT prolongation, even after a 2-month follow-up of electrocardiogram (ECG) report.